Omega-3 oils : applications in functional foods - Hernandez, Ernesto, 1955-; Hosokawa, Masashi, 1966- (AOCS Press, 2011)
This book addresses new applications of omega-3 fatty acids from both plant and marine sources in food supplements and pharmaceuticals and covers three basic areas: structure and function, production and processing, and health effects. The authors review the latest clinical evidence on the impact of consumption of omega-3 polyunsaturated fatty acids on prevalent human diseases such as inflammation-related illnesses in general and cardiovascular illnesses in particular. They also examine technologies to purify marine oils and protect them against oxidation as well as novel techniques for their incorporation into foods.
Keywords: Omega-3 fatty acids.; Functional foods.; elektronické knihy; electronic books